Original paperFrequency of IgE-dependent hypersensitivity to moulds in patients with chronic rhinosinusitis with polyps - Gawlik, Radosław; Czecior, Eugeniusz; Jarząb, Jerzy; Grzanka, Alicja; Cichecka, Ewelina; Sowa, Paweł; Ścierski, Wojciech (Advances in Dermatology and Allergology/Postępy Dermatologii i Alergologii, 2014)
Introduction: The complicated etiology of chronic sinusitis with polyps and frequent allergy to mould is established. Aim: We aimed to investigate the frequency of the IgE-dependent hypersensitivity in this group of patients and prove the need of surgery in allergic chronic rhinosinusitis patients. Material and methods : Forty-two patients (19 females, 23 males) aged 34–73 years (55 ±12.6 years), with chronic sinusitis with polyps were included into the study. Functional endoscopic sinus surgery, laryngological examination, sinus computed tomography scans, and smear from maxillary sinus for microbiological examination were done in all patients. Skin prick tests with common perennial and seasonal inhalant allergens, tIgE and sIgE against moulds were required. Results: Thirty-two of 42 patients (71.4%) were allergic to at least one inhalant allergen. A mean concentration of total IgE was 241.2 ±186.3 kU/l (35.0–708.0 kU/l) and was lower in patients with fungal culture found in sinus mucin than in patients without fungal presence 75.1 ±54.6 kU/l vs. 284.3 ±204.1 kU/l. We found no difference in the number of positive skin prick tests in a group with and without fungal culture. None of patients with fungal culture found in sinuses presented a detectable level of mold sIgE. All patients with fungal vegetation in sinuses required at least two polypectomy procedures. Conclusions : The total IgE concentration was significantly lower in patients with fungal presence in sinuses. Nasal polyps occurred more frequently in patients with fungal presence in sinuses.